A Sociology of Transnational Constitutions Social Foundations of the Post-National Legal Structure - Thornhill, Chris (Social Sciences, 2016)
This book examines the social processes that lead to the evolution of legal norms with global constitutional standing in contemporary society. It makes an important contribution to the sociology of constitutional law, post-legal national legal processes and human rights law. This title is also available as Open Access.